2021
DOI: 10.3390/en15010210
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Critical Pore Radius That Results in Critical Gas Saturation during Methane Hydrate Dissociation at the Single-Pore Scale: Analytical Solutions for Small Pores and Potential Implications to Methane Production from Geological Media

Abstract: We examine the critical pore radius that results in critical gas saturation during pure methane hydrate dissociation within geologic porous media. Critical gas saturation is defined as the fraction of gas volume inside a pore system when the methane gas phase spans the system. Analytical solutions for the critical pore radii are obtained for two, simple pore systems consisting of either a single pore-body or a single pore-body connected with a number of pore-throats. Further, we obtain critical values for pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…The results showed that, in comparison to the phase equilibrium in pure water, ZnO presented a slight thermodynamic inhibitory effect on the formation of hydrates. Tsimpanogiannis et al 31 adopted various porous media materials with different pore structures to study the critical pore diameter that could lead to critical gas saturation during the decomposition process of methane hydrates. They found that the decomposition temperature had a relatively small effect on the critical pore diameter for gas production and that the porous media might have a related impact.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, in comparison to the phase equilibrium in pure water, ZnO presented a slight thermodynamic inhibitory effect on the formation of hydrates. Tsimpanogiannis et al 31 adopted various porous media materials with different pore structures to study the critical pore diameter that could lead to critical gas saturation during the decomposition process of methane hydrates. They found that the decomposition temperature had a relatively small effect on the critical pore diameter for gas production and that the porous media might have a related impact.…”
Section: Introductionmentioning
confidence: 99%
“…The recoverable amount of methane is, however, an issue that is currently under debate [16][17][18]. Methane production from the dissociation of hydrates confined within marine sediments requires a better understanding of the interactions between the dissociation thermodynamics occurring under different types of confinement, hydrate saturations, and the different production schemes (i.e., depressurization, thermal stimulation, hydrate inhibitor injection) [19][20][21][22][23]. Significant challenges need to be addressed in an adequate manner in order to incorporate hydrate deposits into the future energy mix in use [7,24].…”
Section: Introductionmentioning
confidence: 99%